Pengaruh Financial Knowledge dan Financial Attitude Terhadap Keberlangsungan Usaha pada Pelaku UMKM di Kota Bogor - Budi Setiawan, Ade; Sholihah, Nurul; Magdalena Melani, Maria (LPPM Akademi Akuntansi Indonesia, 2024)
This study was conducted to understand the impact of financial knowledge and financial attitude on the sustainability of MSMEs in Bogor. This study is part of a descriptive quantitative study. The sample in this study consists of 100 MSME actors in the city of Bogor. Data was collected through questionnaires distributed to respondents and processed using SPSS. The study results show that 1) Financial Knowledge does not have an impact and is not significant on the sustainability of MSMEs in Bogor; 2) Financial Attitude has an impact and is significant on the sustainability of MSMEs in Bogor; 3) Financial Knowledge and Attitude have an impact and are significant on the sustainability of MSMEs in Bogor.